Power bases and job stress : the impact of mentoring - Liew, Wei Tak (Universiti Malaysia Sarawak (UNIMAS), 2010)
The general objective of this research was to examine the relationship of supervisors’ power bases and subordinates’ stresses with the impact of mentoring. This study was conducted in banks in Kuching. A field study with a sample of 195 respondents in 10 banks in Kuching was conducted to examine three widely hypothesized relationships. Data were collected from the respondents by means of questionnaires. By and large, the outcomes from the analyses have demonstrated partially support for the hypotheses. The first hypothesis which examines the relationship of positional power bases of the leaders and subordinates’ stresses showed that legitimate power of the leaders is positively related to relaxation, reward power of the leaders is positively related to role ambiguity/lack of control and relaxation, and coercive power of the leaders is positively related to role ambiguity/lack of control, overload, and psychological discord. The second hypothesis which examines the relationship of personal power bases of the leaders and subordinates’ stresses showed that personal power of the leaders is negatively related to psychological discord and connection power of the leaders is negatively related to relaxation. The third hypothesis which examines the impact of mentoring on the relationship of power and job stress showed that career support is moderating the relationship of power, such as reward power, personal power and role ambiguity/lack of control, moderating the relationship of reward power and overload, moderating the relationship of power, such as reward power, connection power and psychological xii discord, moderating the relationship of coercive power and relaxation, while psychosocial support is moderating the relationship of power, such as legitimate power, reward power and role ambiguity/lack of control, moderating the relationship of power, such as reward power, coercive power and overload, moderating the relationship of reward power and psychological discord. Inevitably, this research offers a conceptual basis for the effective use of power bases. This research may be useful for those who are in positions of leading, to help them understand more clearly the bases of their own actions, and the possible choices to their actions. Practically, this study points to the fact that Kuching’s supervisors need to be trained in the effective use of power bases.